A fresh approach to interpretation of visible photoluminescence spectra in silicon nanostructures - Sachenko, A.V.; Kryuchenko, Yu.V.; Manoilov, E.G.; Kaganovich, E.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
To understand both multimodal character of stationary photoluminescence (PL) spectra and observed peculiarities in time-resolved PL in low-dimensional Si structures, it is proposed to take into account an additional effect, which has to emerge in such structures due to indirect-bandgap nature of silicon material. The effect implies that the exciton radiative lifetime becomes a nonmonotonous (oscillating) function of the nanocrystal (NC) size. As a result, in the calculated PL spectra the energy distance between PL peaks or PL minima practically determined by the mean NC size, while dispersion in NC sizes plays a minor role. The qualitative agreement between calculated PL spectra and PL spectra observed experimentally in porous silicon and nanocrystalline silicon (nc-Si) films counts in favor of the used
model of radiative exciton recombination.